2020
DOI: 10.1364/oe.403780
|View full text |Cite
|
Sign up to set email alerts
|

Structure-dependent amplification for denoising and background correction in Fourier ptychographic microscopy

Abstract: Fourier Ptychographic Microscopy (FPM) allows high resolution imaging using iterative phase retrieval to recover an estimate of the complex object from a series of images captured under oblique illumination. FPM is particularly sensitive to noise and uncorrected background signals as it relies on combining information from brightfield and noisy darkfield (DF) images. In this article we consider the impact of different noise sources in FPM and show that inadequate removal of the DF background signal and associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 22 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…With a camera exposure time of 100 ms, the total acquisition time for each (monochrome) image was slightly less than 30 s. Colour images were captured by combining images acquired under illumination by red, green, and blue LEDs. Images were reconstructed using a version of the iterative phase retrieval method described by Tian et al [13] modified to reduce background‐related image artefacts [14].…”
Section: Methodsmentioning
confidence: 99%
“…With a camera exposure time of 100 ms, the total acquisition time for each (monochrome) image was slightly less than 30 s. Colour images were captured by combining images acquired under illumination by red, green, and blue LEDs. Images were reconstructed using a version of the iterative phase retrieval method described by Tian et al [13] modified to reduce background‐related image artefacts [14].…”
Section: Methodsmentioning
confidence: 99%
“…For FPM imaging of peripheral blood films we used a 10x/0.3 objective lens, a sample-LED distance of 62 mm (corresponding to a passband overlap of 75% and 𝑁𝐴 1)2 of 0.9). DF background signals were corrected using the method described by Claveau et al 7 . For imaging histological tissue sections we used a 4x/0.16 objective, a sample-LED distance of 87 mm (corresponding to a passband overlap of 69% and 𝑁𝐴 1)2 of 0.7).…”
Section: Imaging Results For Clinical Samplesmentioning
confidence: 99%
“…If the subtracted level is too low the orange peel artefact is not fully removed, if it is too high real sample information is removed from the DF images which reduces the spatial resolution and contrast of the reconstructed image. For imaging relatively sparse, well separated objects (such as cells in a thin peripheral blood film) we have found that a nonparametric 'structure dependent amplification' method is effective 7 . In this approach data redundancy in real space is exploited to create maps to retain useful information in DF images whilst suppressing the background.…”
Section: Optimisation Of Imaging Performancementioning
confidence: 99%
“…For the second kind, in order to overcome the limitation of the traditional GS algorithm, more algorithms [11,12] have been proposed. Moreover, some anti-noise or denoising algorithms [13][14][15] are applied taking the existed noises into consideration. With regard to determine the position of each sub-frequency domain, the simulated annealing algorithm, the quasi Newton algorithm, and the nonlinear regression analysis algorithm are employed to calibrate the position error [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%